Social psychology (Del Mar, Calif. : CRM/McGraw-Hill Films, 1971)
The portion of this film is an example of the experience of two social groups in interaction. Secondly, basic social psychological concepts are introduced with discussion of their possible applications to the social problems presented in the documentary portion of the film
Keywords: Social psychology